Greenhouse gas emissions from a Cu-contaminated soil remediated by in situ stabilization and phytomanaged by a mixed stand of poplar, willows, and false indigo-bush. Issue 11 (2nd November 2017) - Šimek, M.; Elhottová, D.; Mench, M.; Giagnoni, L.; Nannipieri, P.; Renella, G.
ABSTRACT: Phytomanagement of trace element-contaminated soils can reduce soil toxicity and restore soil ecological functions, including the soil gas exchange with the atmosphere. We studied the emission rate of the greenhouse gases (GHGs) CO2, CH4, and N2 O; the potential CH4 oxidation; denitrification enzyme activity (DEA), and glucose mineralization of a Cu-contaminated soil amended with dolomitic limestone and compost, alone or in combination, after a 2-year phytomanagement with a mixed stand of Populus nigra, Salix viminalis, S. caprea, and Amorpha fruticosa . Soil microbial biomass and microbial community composition after analysis of the phospholipid fatty acids (PLFA) profile were determined. Phytomanagement significantly reduced Cu availability and soil toxicity, increased soil microbial biomass and glucose mineralization capacity, changed the composition of soil microbial communities, and increased the CO2 and N2 O emission rates and DEA. Despite such increases, microbial communities were evolving toward less GHG emission per unit of microbial biomass than in untreated soils. Overall, the aided phytostabilization option would allow methanotrophic populations to establish in the remediated soils due to decreased soil toxicity and increased nutrient availability.